Myanmar:Reintegrating into the International Community - Xianghui Zhu (World Scientific Publishing Co., 2016)
Located at the junction of East Asia, South Asia and Southeast Asia, Myanmar is one of the most important countries in the world's geopolitical landscape. Its ongoing political and economic reforms arouse growing concern from the international community, especially great powers like the US, Japan, India and China. Will the demostic reform bring Myanmar back to the international community? How and to which extent does the demostic reform change Myanmar's relations with other countries? This book is based on papers presented at an international conference on Myanmar held at the Institute of Myanmar Studies in Yunnan University, China in 2014. Based on their long-term observation and studies, experts from China, Laos, Myanmar, Germany, Singapore and the US share their opinions on Myanmar's domestic reform and foreign relations, as well as the current situation and future prospect. This book contributes to better understanding of Myanmar in its dramatic political and social transition.